2021
DOI: 10.1111/cup.13982
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional evaluation of dermatopathology fellowship website content

Abstract: mammaglobin. [2][3][4][5][6][7][8] In addition, the vast majority of primary and metastatic breast carcinomas demonstrate CK20-negativity (CK20−) and CK7-positivity (CK7+) by immunohistochemistry. 2-8 Herein, we report a case of metastatic breast carcinoma to the skin with variant CK20+/CK7− immunophenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…2 However, dermatopathologists often require a high index of suspicion for metastatic disease because of overlapping cytoarchitectural features among tumors and rarely aberrant/atypical immunohistochemical profiles. [3][4][5][6][7][8] Breast cancer is the most common tumor leading to the development of cutaneous metastases, accounting for approximately 69% of primary malignancies associated with skin deposits in women. 1 It is reported that up to 23.9% of patients with breast carcinoma can develop cutaneous metastases.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…2 However, dermatopathologists often require a high index of suspicion for metastatic disease because of overlapping cytoarchitectural features among tumors and rarely aberrant/atypical immunohistochemical profiles. [3][4][5][6][7][8] Breast cancer is the most common tumor leading to the development of cutaneous metastases, accounting for approximately 69% of primary malignancies associated with skin deposits in women. 1 It is reported that up to 23.9% of patients with breast carcinoma can develop cutaneous metastases.…”
mentioning
confidence: 99%
“…By immunohistochemistry, tumor cells are, C, positive for CK20 and, D, negative for CK7 (left, normal sweat glands as internal positive control) (A,C,D, original magnification ×200; B, original magnification ×400) mammaglobin. [2][3][4][5][6][7][8] In addition, the vast majority of primary and metastatic breast carcinomas demonstrate CK20-negativity (CK20−) and CK7-positivity (CK7+) by immunohistochemistry. [2][3][4][5][6][7][8] Herein, we report a case of metastatic breast carcinoma to the skin with variant CK20+/CK7− immunophenotype.…”
mentioning
confidence: 99%
See 3 more Smart Citations